A compression method of educational material for special disciplines of technical University - Baslyk, Konstantin P. (Otkrytoe Obrazovanie, 2018)
The article is devoted to the development of a compression method of the educational material for special disciplines of the technical University. The urgency of solving the problem of compression of the educational material, as well as compression of the information in general, is due to the world trends in the development of science and technology, as well as the requirements that modern educational standards impose on the programs disciplines of higher professional education. A review of the works of other authors, in which the problem of compression of educational material has been investigated, is made in the article. The need for new pedagogical developments, practically oriented directly to professional disciplines, was noted. The possibility of compressing the teaching material of a special discipline is ensured by the commonality of the questions studied, as well as the using the same mathematical apparatus, approaches and methods in determining the main relations. The practical orientation of the subject and the readiness of the audience in the natural sciences and general technical disciplines also matter. This is revealed on the basis of the analysis of modern pedagogical technologies and methods of knowledge engineering, as well as special discipline features. The compression method of an educational material, which uses several pedagogical technologies, is developed. The construction of educational process on a large-block basis, the construction of educational process advanced basis, methodical and didactical reconstruction of educational material are used.Deductive and inductive ways of presentation of educational material are also used. Compression is achieved when structuring the educational material of the discipline. Separate sections of the discipline are combined into semantic groups and read in parallel without possible repetitions. The principle of parallel presentation of the material forms the basis of the concept of the developed method of compression. This principle makes it possible to implement an “open architecture” of the method: there is the possibility of prompt correction or expansion of the content of discipline without significant increase in time costs for the presentation. An interpretation of the proposed method as the procedure of graphs theory is given. The structure of the discipline is modeled as a directed weighted graph (the graph of discipline) with the separation of bipartite subgraphs. The educational elements are represented as vertices of the graph. The rib of the graph models the means of the mathematical apparatus, which establishes the connection between the vertices. The vertices weight is detected as a time spent on the explanation of element contents. The rib weight is detected as a time that spent on the explanation of connection between such vertices. Non-adjacent vertices form a bipartite subgraph of educational elements from one semantic group. The properties of adjacency matrix for the graph of discipline were defined in the article. There was proposed the algorithm of the forming graph of discipline with minimum of weight which contains the bipartite subgraphs – semantic groups of elements. Examples of the implementation of the compression method, confirming its universality are given. The bipartite subgraphs of disciplines are constructed for separate sections of disciplines “Building Mechanics”, “Theoretical Foundations of the Finite Element Method” and “Design of Flying Machines”, the principle of the “open architecture” of the method is shown. The testing of the developed method for compliance with the requirements for modern pedagogical technology was conducted. It is shown that the logic of the implementation of the compression method corresponds to the subject logic of the special discipline of the higher technical educational institution, as well as to the logic of mastering the learning material by the students.